Review of Incoherent Digital Holography: Applications to Multidimensional Incoherent Digital Holographic Microscopy and Palm-Sized Digital Holographic Recorder—Holosensor - Tahara, Tatsuki (Frontiers in Photonics, 2022)
We review advancements in incoherent digital holography (IDH) with an image sensor and its applications to multidimensional microscopy and a palm-sized hologram recorder termed “holosensor”. There are two types of representative IDH technique: IDH with a structured illumination and a single photodetector termed optical scanning holography and self-interference IDH. The latter IDH is a technique to obtain an incoherent digital hologram by modulating an incoherent light wave between an object and an image sensor. Multidimensional information such as three-dimensional space and wavelengths is simultaneously recorded without changing optical filters by introducing interferometric techniques invented in laser holography. Applications to high-speed color-multiplexed holographic fluorescence microscopy, single-shot incoherent full-color holographic microscopy with white light, and a palm-sized multidimensional incoherent hologram recorder have been developed using multidimensional IDH systems. Schematics and experimental results obtained using IDH techniques, incoherent holographic microscopy systems, and compact IDH systems are introduced.